Pop Culture in Asia and Oceania - Nadeau, Kathleen M. 1952-; Murray, Jeremy A. (Santa Barbara, California ABC-CLIO, an imprint of ABC-CLIO, LLC, 2016)
"This volume aims to introduce the general reader to various forms of popular culture in Asia and Oceania. Our volume in this series includes topics related to East Asia, South Asia, Southeast Asia, Central Asia, as well as the Pacific islands of Oceania, including Australia and New Zealand, but does not include western Asia, or what is sometimes referred to as the Middle East"--Provided by publisher.
Chronology -- Popular Music -- Books and Contemporary Literature -- Film -- Television and Radio -- Internet and Social Media -- Sports -- Video Games -- Fashion and Couture -- Appendix: Top Ten Lists.
"This book is also available as an eBook"--Title page verso.
Includes bibliographical references (pages 387-390) and index.
Keywords: Popular culture -- Asia; Popular culture -- Oceania; Asia -- Civilization; Oceania -- Civilization; Asia -- Intellectual life; Oceania -- Intellectual life; Asia -- Social life and customs; Oceania -- Social life and customs